2018
DOI: 10.1016/j.conbuildmat.2018.04.092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fly ash characteristics and alkaline activator components on compressive strength of fly ash-based geopolymer mortar

Abstract: The compressive strength of fly ash-based geopolymer mortar (FBGM) made from five different sources of fly ash was examined. The weight ratio of alkaline activator to fly ash content (AL/FA), the weight ratio of sodium silicate to sodium hydroxide (Na 2 SiO 3 /NaOH) and concentration of the NaOH were considered the main parameters. A total of 180 FBGM mixes were prepared and tested for compressive strength. The results indicated that the optimum AL/FA ratio for activating fly ashes was in the range of 0.5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(43 citation statements)
references
References 57 publications
1
32
0
4
Order By: Relevance
“…Obtained results of compressive and flexural strengths for alkali-activated mortars comprise a wide range of results presented by other authors (compressive strength from 2 MPa to more than 120 MPa, flexural strength from below 0.5 MPa to 9 MPa) [65][66][67][68][69][70][71][72]. The lower mechanical properties are either caused by the wrong sand/fly ash ratio [65] or by using only one alkaline activator [66].…”
Section: Flexural and Compressive Strengthssupporting
confidence: 53%
“…Obtained results of compressive and flexural strengths for alkali-activated mortars comprise a wide range of results presented by other authors (compressive strength from 2 MPa to more than 120 MPa, flexural strength from below 0.5 MPa to 9 MPa) [65][66][67][68][69][70][71][72]. The lower mechanical properties are either caused by the wrong sand/fly ash ratio [65] or by using only one alkaline activator [66].…”
Section: Flexural and Compressive Strengthssupporting
confidence: 53%
“…Haidi et al [15] reported that lower amounts of Si 4+ and Na + affect adversely the formation of the coherent structure that consequently reduces the compressive strength. Even if the amount of silicate was higher (300 g), the geopolymerization was not complete at room temperature in 12 h. Thus with the increase of silicate concentration and curing temperature, the compressive strength increased in all the cases (Fig.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Esto se puede atribuir a que la adecuada incorporación de Na2SiO3 en el sistema genera un aporte de sílice adicional (SiO2) lo que conduce a formación de más enlaces Si-O-Si(Azevedo y Strecker, 2017;Lǎzǎrescu et al, 2017). Cuando la proporción Na2SiO3/NaOH es de 2 y 2,50 la resistencia a la compresión disminuye porque el exceso de Na2SiO3 produce más iones de silicio (Si 4+ ) y de sodio (Na + ) de los requeridos, lo que puede saturar la matriz con iones libres produciendo una inadecuada geopolimerización(Hadi et al, 2018). De igual modo, cuando el Si 4+ y el Na + se reduce en el sistema la formación de la estructura geopolimérica se afecta negativamente, lo que genera disminución en la resistencia a la compresión(Hadi et al, 2018), tal como se evidencia en la relación Na2SiO3/NaOH de 1.Las relaciones AA/CV representan el peso total de las soluciones alcalinas (Na2SiO3/NaOH) sobre el peso de la ceniza volante.…”
unclassified
“…Cuando la proporción Na2SiO3/NaOH es de 2 y 2,50 la resistencia a la compresión disminuye porque el exceso de Na2SiO3 produce más iones de silicio (Si 4+ ) y de sodio (Na + ) de los requeridos, lo que puede saturar la matriz con iones libres produciendo una inadecuada geopolimerización(Hadi et al, 2018). De igual modo, cuando el Si 4+ y el Na + se reduce en el sistema la formación de la estructura geopolimérica se afecta negativamente, lo que genera disminución en la resistencia a la compresión(Hadi et al, 2018), tal como se evidencia en la relación Na2SiO3/NaOH de 1.Las relaciones AA/CV representan el peso total de las soluciones alcalinas (Na2SiO3/NaOH) sobre el peso de la ceniza volante. Los resultados mostraron que se obtuvo una mayor resistencia a la compresión cuando se utilizó relación AA/CV 0,45 tal como sucedió en la mezcla optima hallada (GB6-24h).…”
unclassified
See 1 more Smart Citation